Improving childcare quality at scale: the effects of "From Zero to Forever" (2018)
The focus in developing countries has shifted from increasing access to early childhood education to improving its quality. However, large scale studies of childcare quality improvement are scarce. In this paper we study the immediate and medium-term effects of a large-scale expansion of integrated early education services on child development, by analyzing the expansion of the Colombian national early childhood strategy known as "From Zero and Forever" between 2011 and 2013. The results indicate that the increased access to enhanced early education had a large immediate effect on language that still persists five years into the intervention.